Beyond trade creation: Preferential trade agreements and trade disputes. (30th October 2019) - Li, Tan; Qiu, Larry D.
Abstract: This study investigates the effects of preferential trade agreements (PTA) on bilateral trade disputes. We construct a unique and comprehensive dataset on inter‐country trade disputes from 1995 to 2007. The dataset covers 110 countries and 1, 162 bilateral country‐pair trade disputes. Using this dataset in a gravity‐type model of trade dispute analysis, we find that countries belonging to the same PTA tend to experience fewer trade conflicts among themselves than with non‐member countries. By studying various types of PTA with different dispute settlement mechanisms, we further find that the dispute‐reducing effect only comes from PTA with specific provisions on dispute settlement mechanisms. Moreover, the effect is stronger if those PTA explicitly stipulate that members can also resolve their disputes via the WTO Dispute Settlement Body. However, having PTA that do not address how members should resolve their disputes may lead to more dispute initiations than in cases without PTA.